E-certification: financial analysis and European Computer Driving Licence (ECDL) Hellas case. (5th August 2010) - Terzis, Vasileios; Economides, Anastasios A.
The difficult economic situation demands very careful investments plans in education. This paper presents a financial analysis of the e-certification branch. It uses financial ratios in order to measure the liquidity, the activity, the debt and the profitability of the enterprises in the branch. Then it applies these ratios to a case study regarding European Computer Driving Licence (ECDL) Hellas. Moreover, it performs a feasibility analysis for a new entrant in the e-certification market. Using cost-benefit analysis the paper measures the benefit-cost ratio, the payback period, the net present value (NPV), the internal rate of return (IRR) and the break-even point for a new investment in the e-certification branch. Finally, it concludes regarding the present and the future of the e-certification branch in Greece. This paper can be helpful in other business cases in education.